Mapping of higher education units in multicampi institutions: analysis of technological proximity in Centro Estadual de Educacao Paula Souza - Rocha, Regina Ferreira da [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
Higher Education Institutions are considered important pillars for scientific and technological development. In this context, Centro Estadual de Educacao Tecnologica Paula Souza -a multicampi educational institution- is composed of 73 technology colleges allocated in Sao Paulo state. This study aims to analyze the proximities among Centro Paula Souza's units according to their technological vocations, in order to visualize clusters formed from their similarities. As a methodological approach to map the similarity network between the educational units, social network analysis and cluster multivariate statistical analysis are adopted. There are three clusters, from which it is possible to visualize the potential for interaction between the units, their strengths, common aspects, and peculiarities. The results provide input to the decision-making of the institution's academic-scientific management as well as a method of analysis for others with a similar structure.
Keywords: Clusters in Multicampi Higher Education Institutions; Social Network Analysis; Informetrics